Zakat and Waqf Synergies to Accelerating Sustainable Development - Mukhlishin; Jelang Ramadhan; Imam Khomeini Hayatullah (Lembaga Contrarius Indonesia, 2025)
Integrating zakat and waqf offers significant potential to address multidimensional issues such as poverty, social inequality, and sustainable development. However, fragmented management, limited public understanding of productive waqf, and a lack of digital integration hinder the optimization of their synergy. This research explores the integration of zakat and waqf to support Indonesia's Sustainable Development Goals (SDGs), particularly within local communities. Using a qualitative literature review approach, the study analyzes the potential, challenges, and opportunities of zakat and waqf integration through thematic analysis of secondary data from academic articles, institutional reports, and legal documents. The findings indicate that zakat and waqf can meet urgent needs, such as food security and health services, while also funding long-term projects like education and agriculture. However, fragmented governmental management, poor public awareness of productive waqf, and inadequate digital integration hinder their full potential. Digital technology plays a transformative role by enhancing transparency, fostering community participation, and improving the integration of zakat and waqf management. This synergy represents a promising strategy to advance the SDGs in Indonesia. Further empirical studies and technological advancements are recommended to optimize this collaboration and ensure its impact on sustainable development.